Investigation of heat assisted high speed end milling of soda lime glass for surface generation - Konneh, Mohamed; Bagum, Mst Nasima; Amin, Akm Nurul M.Nurul; Asyah, Amira Fatin (Scientific.Net, 2017)
Brittle materials like soda lime glass can be machined in ductile mode under controlled machining conditions (feed rate, depth of cut, small tool edge radius) using high speed to generate a desired surface finish. The heat generated in high speed machining tends to promote ductile machining. In this paper, heat assisted high speed end milling is investigated to explore machinability of the soda lime glass. The heat assisted machining thus generates low surface finish on the machined workpiece. The heat assisted high speed end milling of soda lime was carried out using uncoated 2 flute carbide end mill at a constant depth of cut 25 μm, while the spindle speed and feed rate were varied from 30,000 to 50,000 rpm and 45 to 75 mm/min, respectively. The applied temperature was varied from 200 °C to 300 °C. The observations of machined surface were done on Surf-test (SV-514) and Scanning Electron microscope (SEM). A quadratic model for roughness (Ra) was developed using Central Composite Design of experiment. The optimum Ra, 0.10 μm was achieved at 49,570 rpm, 58 mm/min feed rate and heating temperature at 238°C. It is found that cutting speed has the greatest influence on the surface roughness value, followed by feed rate and heating temperature.